PENGARUH BAURAN PROMOSI DAN DESIGN PRODUK TERHADAP KEPUTUSAN KONSUMEN REMAJA PUTERI DALAM PEMBELIAN HONDA BEAT DI PEKANBARU - Wijaya Saputra; Jushermi '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of partial and simultaneous promotion mix variables and product design to consumer decision girls in the purchase of the Honda Beat in Pekanbaru. The study was conducted on November 2, 2013 to May 20, 2014 in the city of Pekanbaru Riau.Di province in this study consisted of six variables: the one dependent variable and the five independent variables. These variables are the purchase decision (Y), Advertising (X1) Private Sales (X2) Sales Promotion (X3) Publicity (X4) Product Design (X5). The study was conducted using a sample of 100 people. Research using purposive sampling technique. While the data analysis, research using multiple linear regression analysis using SPSS (Statistical Package for Social Science) version 20.0. Known the results of research promotional mix and product design positive and significant influence on consumer decisions girls in the purchase of the Honda Beat in Pekanbaru either simultaneously maupaun partially. While for the most dominant variable pengaruhmya girls to consumer decision in purchasing a Honda Beat in Pekanbaru is the advertising variable. So advertising, personal selling, sales promotion, publicity, and attractive product design can improve the decisions of consumers girls in the purchase of the Honda Beat in Pekanbaru, so perlua conduct an evaluation to make changes on an ongoing basis to make advertising more attractive to consumers, while for design products can conduct a survey to determine the wants and needs of consumers on the desired design.Keywords: Advertising, Personal Selling, Sales Promotion, Publicity, Product Design, Purchase Decision